2009
DOI: 10.1007/s00403-009-0968-0
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E gene polymorphism in psoriasis

Abstract: Polymorphism in the apolipoprotein E gene has been associated with several neurological, cardiological and ophthalmological diseases. Apolipoprotein E is involved in psoriasis by modifying mitogen-activated T lymphocyte proliferation and by assuring protection against some infections. We evaluated the apolipoprotein E gene polymorphism in patients suffering from psoriasis (compared to matched controls) in Thrace, Northern Greece. One hundred and forty patients suffering from psoriasis vulgaris and 155 matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
2
12
1
Order By: Relevance
“…Zervou et al (2009) found a weak association between the T allele in rs7574865 ( STAT4 ) and predisposition to psoriasis (Table 1) [72]. APOE may play a role in psoriasis by modifying the proliferation of mitogen-activated T lymphocytes and ensuring protection against some infections (Figure 1) [73]. Other authors have reported the APOE- ε 4 allele to be a risk factor for the development of severe form of psoriasis [74].…”
Section: Genetics Of Psoriasismentioning
confidence: 99%
“…Zervou et al (2009) found a weak association between the T allele in rs7574865 ( STAT4 ) and predisposition to psoriasis (Table 1) [72]. APOE may play a role in psoriasis by modifying the proliferation of mitogen-activated T lymphocytes and ensuring protection against some infections (Figure 1) [73]. Other authors have reported the APOE- ε 4 allele to be a risk factor for the development of severe form of psoriasis [74].…”
Section: Genetics Of Psoriasismentioning
confidence: 99%
“…They have a different molecular structure, amino acid composition, and antiatherosclerotic properties. In psoriatic patients, different results concerning apolipoproteins apoA1, apoB, and apoE were presented [16, 41, 66, 67]. Apolipoprotein A1 has been immunocytochemically detected at the psoriatic skin dermoepidermal junction, vascular walls, and the perivascular region of papillary dermis.…”
Section: Apolipoproteinsmentioning
confidence: 99%
“…Apolipoprotein E (ApoE) is a glycoprotein involved in the regulation of triglycerides and low-density lipoprotein (LDL) levels [67]. ApoE can modulate mitogen-activated T-lymphocyte proliferation in vitro and provides protection against some infections [82, 83].…”
Section: Apolipoproteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…ApoE is mainly produced in the liver, but other organs and tissues such as the brain, spleen, kidneys, gonads, adrenals, and macrophages also produce this protein (Mahley, 1988). Accumulating evidence reveals that the polymorphism of the apoE gene is genetically associated with many diseases, including essential hypertension (EH), coronary artery disease, polycystic ovary syndrome, Alzheimer's disease, psoriasis, vascular dementia, gallbladder stone disease, and cerebrovascular disorders (Karpouzis et al, 2009;Chaudhary et al, 2012;Liu et al, 2012a;Xue et al, 2012;Yin et al, 2012;Zhou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%